1995
DOI: 10.1093/ajcp/103.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reproducibility of the Nottingham Modification of the Bloom and Richardson Histologic Grading Scheme for Infiltrating Ductal Carcinoma

Abstract: The interobserver reproducibility of the Nottingham modification of the Bloom and Richardson histologic grading scheme for invasive breast carcinoma was tested. Six surgical pathologists from four institutions independently evaluated histologic grade and each of its three components for 75 infiltrating ductal carcinomas. The number of slides per case ranged from one to nine (median 3). Pairwise kappa values for agreement ranged from moderate to substantial (0.43-0.74) for histologic grade. Generalized kappa va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
2
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(161 citation statements)
references
References 0 publications
6
144
2
5
Order By: Relevance
“…Although Frierson et al 10 reported moderate to substantial k values for interobserver agreement for histologic grade, Delides et al 9 found low interobserver agreement and overall k values for the European Working Group and for the Japan National Surgical Adjuvant Study were moderate at best. [8][9][10][11] Interobserver and intraobserver agreement, as well as accuracy of classification relative to the reference standard were higher for the grade I and grade III tumors than for the grade II tumors. These results are similar to those of Dalton et al, 12 who showed that excellent agreement for histologic grade was more likely to occur for extremely low-grade and extremely high-grade cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Frierson et al 10 reported moderate to substantial k values for interobserver agreement for histologic grade, Delides et al 9 found low interobserver agreement and overall k values for the European Working Group and for the Japan National Surgical Adjuvant Study were moderate at best. [8][9][10][11] Interobserver and intraobserver agreement, as well as accuracy of classification relative to the reference standard were higher for the grade I and grade III tumors than for the grade II tumors. These results are similar to those of Dalton et al, 12 who showed that excellent agreement for histologic grade was more likely to occur for extremely low-grade and extremely high-grade cancers.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[12][13][14] In at least one series, it was suggested that pathologists who are not specialists in breast disease tend to underscore, possibly due to a preconception that invasive breast cancer sorts equally into each of the three grades. 15 It has also been argued that reproducibility of nuclear pleomorphism is difficult because of the nonquantitative nature of the scoring method, 16 but in our opinion, the intermediate nature of some breast cancers and the heterogeneity in nuclear pleomorphism that can occur in these malignancies is underappreciated and probably contributes to the relatively high and variable degree of interobserver disagreement, especially with respect to the intermediate grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…by modified Bloom-Richardson criteria (40). Amplification of CCND1 is seen clearly in nuclei of both the touch preparations and the LCM specimens, whereas the RB1 signal is present at the usual two to four copies per cell.…”
Section: Resultsmentioning
confidence: 92%
“…When addressing only ipsilateral breast tumour recurrences with conserved histological types, we showed a good concordance with their primary tumours in terms of hormonal receptors but the absence of any concordance in terms of histological grade and its components. Bearing in mind the inter-observer disagreement (Frierson et al, 1995;Robbins et al, 1995), there is always the concern that it could reflect an intra-observer variability in the definition of the histological grade.…”
Section: Discussionmentioning
confidence: 99%